KONSTRUKSI REALITAS KECERDASAN ANAK: ANALISIS SEMIOTIK BARTHES IKLAN SUSU FORMULA ANAK DI TELEVISI - Rahman Asri (Universitas Tidar, 2018)
The aim of this research to identify messages in growing up milk TV commercial. This study use content analysis and semiotic analysis from Roland Barthes who emphasis interaction between textual with personal experiences and cultural behavior. Impact of growing up milk advertisement give ‘message’ to mothers as audience target that growing up milk consumption make their children as a winner, super kid, genius, best achiever on study and their dreams. The advertisement was constructed children intelegent reality on mothers which correlated growing up milk consumption as seen on TV commercial. Keywords: semiotic analysis, media effect, advertising, children, television